PENGGUNAAN MODEL RASCH UNTUK ANALISIS INSTRUMEN TES PADA MATA KULIAH MATEMATIKA AKTUARIA - Azizah, Azizah; Wahyuningsih, Sapti (Jurnal Pendidikan Matematika (JUPITEK), 2020)
This research was conducted to analyze the test instruments used to measure the ability of students in actuarial mathematics courses in mathematics department, State University of Malang. Participants in this course consist of 40 students. The form of questions given were multiple choice questions totaling 50 items related to the premium calculation material on life insurance. The Rasch model is used to get fit items. This analysis is carried out with the help of Winsteps software. From the Winsteps program output, 25 items were obtained fit to the Rasch model with an average MNSQ Outfit score for person and item 0.98 and 0.98, respectively. While the Outfit ZSTD value for person and item are 0 and -0.01 respectively. While the reliability of the instrument stated in alpha cronbach is 0.85